Pengaruh Burnout terhadap Kinerja Pelayanan Publik Kader Surabaya Hebat di Kelurahan Tembok Dukuh Kota Surabaya - Muhammad Adrian Fans Gymnastiar; Meirinawati Meirinawati (Studi Administrasi Publik dan ilmu Komunikasi, 2025)
Public service is an activity or a series of efforts to fulfill the service needs of the community. The public services received by the community come from the government's performance in providing services, which must be excellent and consistent. One of the public services in society is provided by Kader Surabaya Hebat, an organization that serves the community at the smallest level of government. Various issues arise, including workload, lack of training, and inadequate appreciation compared to the workload given. These factors contribute to problems such as work stress or burnout. The tendency for burnout or work stress can be experienced by public service workers due to high work pressure and job demands. Additionally, the work environment also significantly affects the emergence of burnout. Thus, the research problem raised in this study is how burnout affects the public service performance of Kader Surabaya Hebat in Tembok Dukuh Village, Surabaya City. The purpose of this research is to describe and analyze the effect of burnout on the public service performance of Kader Surabaya Hebat in Tembok Dukuh Village, Surabaya City. This study employs a descriptive research type with a quantitative approach and data analysis techniques using the Simple Linear Regression method. The results of this study indicate that burnout or work stress has a significant influence, with a strength of 83.4%, classified as very strong, and has a negative impact on the public service performance of Kader Surabaya Hebat in Tembok Dukuh.